Persisting in the Age of COVID-19: School-University Partnership to Promote Equity-Oriented Teaching and Learning - Susan Y. Leonard; Gayle Andrews; Allie Loder; Taera OConnor; Brooke Wilson (Middle Grades Review, 2022)
The authors describe collaborative efforts between novice teachers and their former university teacher educators who partnered to design and enact equity-oriented teaching and learning experiences for teacher candidates and young adolescents despite limitations, barriers, and disruptions generated by COVID-19. Observations and feedback from students, teachers, and leaders speak to mutual benefits that the partnership generated. Authors will describe their collaborative processes, feature artifacts from the activities, and discuss implications for future practice.
Keywords: middle grades education; school-university partnership; COVID-19; equity-oriented; teacher education; teacher candidates; preservice teachers; young adolescents; technology; real-world